The Influence Of Work Skills, Communication, Supervision, Work Quality, Support Facilities And Work Load On The Work Achievement Of Employees In The Protocol And Communication Section Of Lahat Regional Secretary Leaders - Huljanah, Witari Miftha; Hamid, Abdul; Basyith, Abdul (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
The research was carried out by the author with the aim of knowing and analyzing the influence of work skills, communication, supervision, work quality, supporting facilities and workload individually and collectively on the work performance of employees of the Protocol and Communication Section of the Lahat Regional Secretary. The research method used in this research is a quantitative method using questionnaires distributed to respondents. Test data quality using validity tests, reliability tests, normality tests. The analysis used is descriptive analysis and inferential analysis using statistical calculations with multiple regression formulas, partial simultaneous tests and coefficient of determination. The research results showed that work skills, communication, supervision, work quality, supporting facilities and workload had a significant effect individually and collectively on the work performance of employees of the Protocol and Communication Section of the Lahat Regional Secretary.